Embedded C programming: a practical course introducing programmable microprocessors - Laverty, David M.; Milliken, Jonny; Milford, Matthew; Cregan, Michael (European journal of engineering education, 2012)
This paper presents a new laboratory-based module for embedded systems teaching, which addresses the current lack of consideration for the link between hardware development, software implementation, course content and student evaluation in a laboratory environment. The course introduces second year undergraduate students to the interface between hardware and software and the programming of embedded devices; in this case, the PIC (originally peripheral interface controller, later rebranded programmable intelligent computer) microcontroller. A hardware development board designed for use in the laboratories of this module is presented. Through hands on laboratory experience, students are encouraged to engage with practical problem-solving exercises and develop programming skills across a broad range of scenarios.